Monitoring of biosolid application trials in Eucalyptus globulus plantation, in Central Chile - Donoso, Sergio; Peña-Rojas, Karen; Galdames, Evelyn; Pacheco, Cristián; Espinoza, Claudia; Durán, Sergio; Gangas, Rodrigo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
Fertilization with biosolid is an option for beneficial use of waste generated from wastewater treatment plant. At this point of view, it is necessary know its effect in forest plantations. The study was established in two sectors with plantations of Eucalyptus globulus (blue gum), in the Región Metropolitana de Santiago: 1) 12 years old plantation, without silvicultural interventions; 2) coppice 2 years old, with multiple sprouts by stump. Were evaluated three amounts of biosolids applications: T0 (addition of 0 Mgha-1), T30 (30 Mgha-1), T50 (50 Mgha-1). In each plantation diameter growth, predawn water potential and relative water content during four years and leaf nutritional status of the trees during two years were measured. The main results showed the improvement in the predawn water potential of trees fertilized with biosolids in the 12 years old plantations. The sector of coppice showed no significant differences in the variables evaluated, as this comes from shoots of harvested stools, taking lots of root mass which provides water and nutritional requirements for the trees.